Written role models in professionalism education. Issue 2 (30th November 2007) - Coulehan, J
Abstract : After more than a generation of neglect in medical education, professionalism has now been restored to the classroom and clinic. However, the current emphasis on teaching and evaluating professionalism in clinical education risks failure because of the large gap between explicit professional ideals and today's culture of medical education. For professionalism curricula to be successful, they must be narrative-based, rather than rule-based. This requires substantial increases in appropriate role modeling, opportunities to develop self-awareness, development of narrative competence and investment in community service. Fictional and non-fictional written narratives can play an important supplemental role throughout medical training by introducing additional role model physicians and, more importantly, by promoting discussion and analysis of professional virtue in practice. Using "The Steel Windpipe", "Darkness", "Malingerers" and "The Good Doctor" as examples, the author illustrates the use of short stories to help medical students explore the meaning of professionalism from a narrative perspective.